Perancangan Aplikasi Panic Button BPBD Kota Langsa Untuk Kesiapsiagaan Bencana Banjir Kota Langsa - Muammar, Ahda; Munawir; Harianto, Dimas; Febiola, Salsabilla; Rifqi Ramadhan, Muhammad (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
Floods often occur due to heavy rainfall. The area of the city of Langsa, Aceh is one of the cities that is often affected by natural floods. Several low-lying areas in Langsa city are inundated by floods when rainfall is high. The impact of this natural disaster is quite detrimental and disrupts residents' activities if the flood comes suddenly. According to the Regional Disaster Mitigation Agency for the city of Langsa, five sub-districts were submerged in floods until the water level reached 100 cm. Uses RESTful technology to exchange data with JSON forms via URIs (Uniform Resource Identifier). In this study, the authors were able to produce a website that is centralized by utilizing the REST API web service method in the data retrieval process which aims to combine or unify these data even though they come from different databases. This research will explain how to implement the Panic Button android application in flood disaster preparedness that occurred in the city of Langsa.